KORELASI ANTARA PERTAMBAHAN BERAT BADAN SELAMA KEHAMILAN DENGAN BERAT BAYI SAAT LAHIR DI PUSKESMAS MENINTING KABUPATEN LOMBOK BARAT - Primayanti, Ika; Danianto, Ario; Wilmayani, Ni Ketut; Geriputri , Ni Nyoman (Faculty of Medicine Universitas Mataram, 2020)
Background: Maternal weight before pregnancy as one of maternal nutritional status illustration, has a close relationship with baby birth weight. Weight gain during pregnancy is an illustration of the fetus rate of growth need to be considered because the increase in weight that is lacking or excessive may cause serious problems for infants and mothers. This study aims to determine the correlation of early pregnancy nutritional status and baby birth weight. Methods: The research design was observational analytic with cross sectional approach. The research data were obtained from maternal cohorts, maternal cards and cohorts of infants who underwent antenatal care between July 2017–January 2018 at polindes in Meninting Primary Health Care territory. Data were analyzed by Spearman correlation test. Results: One hundred and fifty data were enrolled in this study, with the majority age group of 20–35 years (78%) and multigravida status (71%). Statistical analysis showed no correlation between maternal weight gain and birth weight (p <0.05). Conclusion: maternal weight gain during pregnancy is not the only factor that contributes to the baby's weight at birth Keywords: maternal weight gain, birth weight